World Workshop on Oral Medicine VII: Non‐opioid pain management of head and neck chemo/radiation‐induced mucositis: A systematic review. (29th May 2019) - Christoforou, Janina; Karasneh, Jumana; Manfredi, Maddalena; Dave, Bella; Walker, Jennifer S.; Dios, Pedro Diz; Epstein, Joel; Kumar, Navdeep; Glick, Michael; Lockhart, Peter B.; Patton, Lauren L.
Abstract: Objective: To evaluate the current evidence regarding the effectiveness of non‐opioid interventions for the therapeutic management of pain in head and neck cancer patients with oral mucositis resulting from radiotherapy only or chemoradiotherapy. Materials and Methods: A literature search was conducted which included randomised controlled trials that assessed patient‐related outcome of pain in patients with oral mucositis associated with radiation therapy only or chemoradiotherapy. Literature searches were conducted in MEDLINE via Pubmed, Embase, Scopus and CINAHL. Results: The electronic searches identified 846 articles. Screening revealed that six articles met all eligibility inclusion criteria. Interventions showing statistically significant benefits to reduce oral mucositis associated pain compared to placebo included doxepin ( p < 0.001, 95% CI −6.7 to −2.1), amitriptyline ( p = 0.04), diclofenac ( p < 0.01) and benzydamine ( p = 0.014). Conclusions: Non‐opioid interventions, including topical doxepin, amitriptyline, diclofenac and benzydamine, were found to provide relief of pain due to mucositis, and when effective may allow for reduction in the use of opioids in pain management.